Soil nematode community assembly in a primary tropical lowland rainforest - Hou, Weichen; He, Mengfei; Qi, Yanwen; Liu, Tiedong; Luo, Jinhuan (Frontiers in Ecology and Evolution, 2022)
Conversion of tropical lowland rainforest to agricultural land (e.g., rubber plantation) has resulted in more than half destruction for global tropical lowland rainforest. Thus it is urgent to perform ecological restoration in tropical lowland rainforest. The first step of restoration is to recover soil functioning (i.e., soil fertility, carbon and nitrogen cycling). This requires understanding community assembly of soil nematode communities which has never been explored in tropical lowland rainforest. Here, we measured species compositions of plant and soil nematode communities and soil characteristics (pH, total and available nitrogen, and phosphorus, and soil water content) in a primary tropical lowland rainforest which is located in Hainan Island, China. We utilized two tests (null-model test and distance-based Moran’s eigenvector maps (MEM) and redundancy analysis-based variance partitioning) to quantify the relative contribution of deterministic processes (abiotic filtering and biotic interactions) and stochastic processes (random processes and dispersal limitation) to soil nematode community. We found that deterministic process (habitat filtering) determined community assembly of nematode community in our tropical lowland rainforest. Moreover, soil properties but not plant diversity was the key determinant of nematode community assembly. Our result is for the first time to disentangle community assembly of nematode community in tropical lowland rainforest. This quantified community assembly mechanism can guide future soil functioning recovery of tropical lowland rainforest.